2016
DOI: 10.5455/jice.20160923100120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herbal medicine on human uterine tumor-bearing nude mice

Abstract: Aim:Uterine leiomyomas are the most common benign uterine neoplasms associated with significant morbidity. Herbal formulas capable of restoring yin-yang balance by dispersing blood stasis may be useful for managing fibroid symptoms.Materials and Methods:In this study, the antitumor properties of three herbs viz., Trogopterus xanthipes Milen-Edwards, Paeonia lactiflora Pallas, and Ulmus davidiana Planch were evaluated in nude mice injected intravenously with human malignant myomas. Tumor fragments were xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Evidence has reported that six methyl ester derivatives isolated from the root of Radix Kansui, including 11,13‐eicosadienoic acid methyl ester, 12‐octadecenoic acid methyl ester, (Z, Z)‐methyl ester‐9,12‐octadecadienoic acid, 10‐methyl‐heptadecanoic acid methyl ester, hexadecanoic acid methyl ester, and methyl ester‐5‐oxo‐DL‐proline, can inhibit the growth of human gastric cancer cell, SGC‐7901, by inducing apoptosis 36 . Notably, the major functional component of Radix Paeoniae Alba ( Paeonia lactiflora ), paeoniflorin, was found to have anticancer activity on various human cancers, including liver cancer, lung cancer, bladder cancer, pancreatic cancer, breast cancer, uterine cancer, and glioblastoma 37–43 . For centuries, Pinelliae Rhizoma Praeparatum is also used for treating cough, phlegm, and cancer 21,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has reported that six methyl ester derivatives isolated from the root of Radix Kansui, including 11,13‐eicosadienoic acid methyl ester, 12‐octadecenoic acid methyl ester, (Z, Z)‐methyl ester‐9,12‐octadecadienoic acid, 10‐methyl‐heptadecanoic acid methyl ester, hexadecanoic acid methyl ester, and methyl ester‐5‐oxo‐DL‐proline, can inhibit the growth of human gastric cancer cell, SGC‐7901, by inducing apoptosis 36 . Notably, the major functional component of Radix Paeoniae Alba ( Paeonia lactiflora ), paeoniflorin, was found to have anticancer activity on various human cancers, including liver cancer, lung cancer, bladder cancer, pancreatic cancer, breast cancer, uterine cancer, and glioblastoma 37–43 . For centuries, Pinelliae Rhizoma Praeparatum is also used for treating cough, phlegm, and cancer 21,44 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Notably, the major functional component of Radix Paeoniae Alba ( Paeonia lactiflora ), paeoniflorin, was found to have anticancer activity on various human cancers, including liver cancer, lung cancer, bladder cancer, pancreatic cancer, breast cancer, uterine cancer, and glioblastoma. 37 , 38 , 39 , 40 , 41 , 42 , 43 For centuries, Pinelliae Rhizoma Praeparatum is also used for treating cough, phlegm, and cancer. 21 , 44 Interestingly, N‐oxalylglycine (NOG), known as a 2‐oxoglutarate (2OG) inhibitor, is a natural derivate of Rheum rhabarbarum and has been found to reveal anticancer activity by silencing the overexpressed alkylation repair protein‐B (AlkB) in cervical carcinoma and head and neck squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%